Internet advertising as an important tool for business development - Кифяк, Олександр; Kyfyak, Viktoria; Петренко, Оксана; Гарват, Ольга; Білоусько, Таміла (MAGNANIMITAS, 2022)
The relevance of the research topic lies in improving the quality of entrepreneurial activity in the conditions of an uncertain environment and geopolitical challenges. The importance of developing a high-quality enterprise strategy is determined by several negative factors in the corporate market of many countries. Digital technologies, as a product of human scientific and technical progress, greatly simplify entrepreneurial activities, and Internet advertising ensures long-term viability on the market. Using Internet advertising and special software has become a key factor in the development of entrepreneurial activity in current conditions. It was with the help of the formation of quality strategies and innovative approaches to developing a digital marketing strategy that it was possible to improve the features of the enterprise’s activities in a global environment. The purpose of the academic paper is to study the use of Internet advertising in a real example and outline the fundamental principles of its implementation. The research objective is to analyze the essence of the definition of Internet advertising in the context of an uncertain environment on the market and to study the key advantages and disadvantages of using Internet advertising. The research object is Internet advertising as a modern innovative tool for implementing the enterprise’s marketing policy and strategy. The research methodology consists of the possibility of forming qualitative approaches to developing entrepreneurial activity and using open software for digital marketing. The obtained research results can improve the planning of business activities and stimulate the development of their web resources as prerequisites for implementing effective Internet advertising. The academic paper investigates the features of implementing Internet advertising. Thus, the scientific article provides several practical results for the possibility of using Internet advertising by entrepreneurs in European countries.
Keywords: digital marketing, internet advertising, advertising budget, conversion, indexing, SEO optimization, search engines, websites